Review Literatur : Optimalisasi Kemampuan Koneksi Matematis Siswa dengan Menggunakan Pendekatan Saintifik - Muzaki, Ahmad (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2021)
The purpose of this study was to determine the optimization of students' mathematical connection skills using a scientific approach. The method used is library research. The data in this study were obtained through reading, taking notes, and collecting data from various library sources such as journals, articles and other relevant sources. The results of the study, students' mathematical connection abilities can be optimized by using a learning model with a scientific approach. The learning steps taken include: observing, asking questions, gathering information, processing information and communicating.